1989
DOI: 10.1002/chin.198945155
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Alkylation of Pyrazoles and 1,2,4‐Triazole with cis‐ and trans‐1,4‐Dichloro‐2‐butene Under Phase‐Transfer Conditions.

Abstract: Reaction of the pyrazoles (I) with excess cis‐1,4‐dichloro‐2‐butene (II) gives the bicyclic salts (III), whereas with excess trans‐1,4‐dichloro‐2‐butene (IV) the mono‐substituted products (V) and (VI) are obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The same we earlier observed in alkylation of pyrazoles with cis-1,4-dichloro-2-butene [5]. Compounds V3VII were converted into monomeric N-(2-vinyloxyethyl)pyrazoles VIII3X by dehydrochlorination with a super base (potassium hydroxide + DMSO), since HCl could be eliminated neither in alcoholic alkalis [6] nor in phase-transfer conditions [5,7].…”
Section: äääääääääääämentioning
confidence: 58%
See 1 more Smart Citation
“…The same we earlier observed in alkylation of pyrazoles with cis-1,4-dichloro-2-butene [5]. Compounds V3VII were converted into monomeric N-(2-vinyloxyethyl)pyrazoles VIII3X by dehydrochlorination with a super base (potassium hydroxide + DMSO), since HCl could be eliminated neither in alcoholic alkalis [6] nor in phase-transfer conditions [5,7].…”
Section: äääääääääääämentioning
confidence: 58%
“…Compounds V3VII were converted into monomeric N-(2-vinyloxyethyl)pyrazoles VIII3X by dehydrochlorination with a super base (potassium hydroxide + DMSO), since HCl could be eliminated neither in alcoholic alkalis [6] nor in phase-transfer conditions [5,7]. It was found that elimination is accompanied by hydrolysis yielding alcohols XIII.…”
Section: äääääääääääämentioning
confidence: 99%
“…The general prerequisite for the successful usage of ethylene compounds in nucleophilic addition reactions is the presence of electron-withdrawing groups at the double bond, which are activating them towards the nucleophilic attack [1][2][3][4][5][6][7][8][9][10].…”
mentioning
confidence: 99%